RETRACTED: Ghrelin concentration before and after bariatric surgery - Galimov Oleg; Khanov Vladislav; Nasirova Kseniya; Galimov Dmitriy; Ibragimov Tel’man; Titova Tatyana; Titova Anastasiya; Ziangirov Robert; Sufiyarov Rinat (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001